A CRITERION-REFERENCED TEST BATTERY TO ASSESS OVERALL ABILITY IN TEAM HANDBALL - Shoukeh, Nart A.; Mismar, Bassam A.; Al Dmour, Hisham Ali (European Scientific Journal, ESJ, 2013)
The main purpose of the study was to construct the team handball skill test battery, based on criterion measurement in order to evaluate the overall ability of pertinent skills for rudimentary level in the game. Ss were ( N=60) students from the faculty of physical education at Yarmuk University in the northern part of the Hashemite Kingdom of Jordan. Those Ss were chosen purposively while registering in 2 team handball classes, each of which had (n=30) students during the academic year 2011/2012. The researchers utilized descriptive methodology by designing the proposed test battery, which comprises of (overhead pass, ball catching and shooting with forward jump) and represents the overall ability of individuals in the game. In order to achieve the objective of the study, selected procedures and techniques have been used to check for scientific coefficient of the tool based on criterion referenced tests and measurement, with considering some indicators such as validity, reliability, and objectivity. Data were collected by examining the Ss of the study throughout using the proposed tests battery at the end of the course. The results revealed that the skill tests battery was valid , reliable, objective, and could be a practical tool to obtain certain and similar objectives. The study recommends adopting this tests battery with the criterion –referenced based measurements to assess overall ability in team handball by assigning students to mastery and none-mastery states.